Injury Rates in Fly-Fishing: An Analysis of Contributing Factors - Andrea Cripps; Jason Smith; Ian Thomas; Trent Griner (Bowling Green State University, 2023)
The sport of fly-fishing has experienced significant growth since the start of the COVID-19 pandemic. There is very little literature available to quantify injuries associated with the sport of fly-fishing. Previous injury surveillance studies demonstrated certain casting styles and equipment may lead to upper extremity pain or injury. The purpose of this study was to evaluate factors that can contribute to injuries that occur while participating in the sport of fly-fishing.